Efficacy of Ticagrelor Monotherapy in Patients at High Bleeding Risk Undergoing Percutaneous Coronary Intervention: a Systematic Review - Erlita Nur Arifana; Bambang Subakti Zulkarnain (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) prevents ischemic events. However, prolonged therapy increases the risk of bleeding. In this context, an antithrombotic strategy is applied to post-PCI patients by discontinuing aspirin and maintaining P2Y12 receptor monotherapy. Currently, patients with ACS treated with the single antiplatelet agent ticagrelor prefer to apply DAPT for 1 to a few months to open blocked arteries. Objectives: This systematic review aimed to evaluate the clinical efficacy of transitioning high-bleeding-risk patients to ticagrelor monotherapy following a three-month course of DAPT. Methods: A systematic literature review based on the PRISMA statement was conducted to review articles on DAPT, PCI, ticagrelor monotherapy, and high bleeding risk (HBR). The article search was conducted using Internet search databases, including PubMed and ScienceDirect, published between January 2014 and December 2024. Results: Six studies met the inclusion criteria and were included in the analysis. Clinical outcomes were assessed over a follow-up period of up to one year, including endpoints such as all-cause mortality, myocardial infarction, stent thrombosis, stroke, and target vessel revascularization. The secondary endpoints included major adverse cardiovascular and cerebrovascular events (MACCE), significant bleeding defined by Bleeding Academic Research Consortium (BARC) types 2, 3, or 5, and net adverse clinical events (NACE). Conclusion: the use of ticagrelor monotherapy after 3 months of dual antiplatelet therapy is expected to assist healthcare professionals in considering the risk-benefit of single therapy for patients after percutaneous coronary intervention.